Evaluation of an alternative positive control strain of Salmonella enterica subsp. enterica serovar Typhimurium for microbial assays. - Yu-Si Lee; Su-Hyeon Joung; Yongchjun Park; Seung Hwan Kim; Soon Han Kim; Insun Joo; Eun Sook An (PLoS ONE)
Officially certified microbiological testing methods utilize positive control strains to enhance experimental reproducibility and ensure standardized procedures among experimenters. Salmonella enterica subsp. enterica serovar Typhimurium ATCC 14028 is designated as a positive control strain for microbiological testing by the International Organization for Standardization, the Korean Pharmacopoeia, and Ministry of Food and Drug Safety (MFDS) foodborne investigation methods. However, using such foreign strains involves complicated import procedures and significant financial burdens. In this study, we aimed to select a domestic isolate strain that can replace S. Typhimurium ATCC 14028. The target strains used were S. Typhimurium strains preserved in the Korean Culture Collection for foodborne pathogens (MFDS). To confirm the equivalent characteristics between the candidate strains and the positive control strain, biochemical and molecular characterization were performed according to the methods specified in ISO test methods, the Food Code, and the MFDS food poisoning investigation methods. After biochemical and molecular biological analyses on 19 S. Typhimurium strains, only those exhibiting equivalent characteristics underwent whole-genome sequencing. In the biochemical characterization, two strains showed different results in the citrate utilization test. Excluding these, the remaining 17 strains were subjected to molecular analysis (PCR), and all showed identical genetic profiles to the positive control strain. Ultimately, whole-genome sequencing of the 17 selected candidate strains revealed that strains 1004022 and 1004023 shared the same sequence type (ST19) as S. Typhimurium ATCC 14028, exhibited fewer than 20 SNPs, and showed 99.94% genomic homology. Therefore, S. Typhimurium MFDS 1004022 and 1004023 were proposed as suitable domestic alternative to the imported strain. It is anticipated that the distribution of these alternative strains to microbiological testing laboratories will contribute to food safety management by supporting microbial testing and analysis.